O problema de se narrar a experiência e a possibilidade da escrita historiográfica no pensamento de Paul Ricoeur - Bubols, Carlos Frederíqui Dias (2020)
In view of the relationship and the limits between experience and historiographical and fictional narratives, some philosophical traditions, such as existentialism and narrativism, have provided antagonistic answers to the questions involved. This dissertation intends firstly to present the main arguments and problems arising from these different positions, and then to advance a preliminary hypothesis of what may be spelled out as a more definite answer to these problems in a future work. The hypothesis is based on the hermeneutic conception that Paul Ricoeur (1913-2005) develops in his Time and Narrative (1984). The first perspective to be examined, namely, existentialism, ― which can be found in Jean-Paul Sartre’s (1905-1980) literary work The Nausea (1938), in his philosophical essay The transcendence of the Ego: An Existentialist Theory of Consciousness (1936) and finally, in his magnum opus Being and Nothingness (1943) ―, understands that life does not have a prior intelligible structure, leaving to the narrators the task of putting together those atomized fragments of life that by themselves have no purpose or meaning. According to the narrativist thought, on the other hand, narrative structures give shape to life in such a way that singular subjects, in isolation, remain unintelligible, meaning being found only within the bounds of that previous and coherent structure of relationships and events. Finally, Paul Ricoeur is at the third level of analysis of this study, in proposing a dialectical relationship between the two previous and antagonistic poles, so that his theory is taken here as a preambular hypothesis for overcoming the tensions between life and narrative such as generated by the existentialist stance, on the one hand, and the supposed reduction of life to a mere narrative, in the narrativist thinking, on the other hand. This discussion also finds reverberations within the theory of history, setting relevant questions with respect to the possibility of meaningful and consistent historiographical writing from the point of view of the scientific and methodological accuracy that it is expected to fulfill. This work will therefore indicate more specifically some alternative ways open to historiographical disciplines in view of keeping its dignity and relevance safe from debasement and depreciation as a valuable human knowledge and practice.